Citrus Genetic Transformation: An Overview of the Current Strategies and Insights on the New Emerging Technologies - Conti, Gabriela; Xoconostle-Cázares, Beatriz; Marcelino-Pérez, Gabriel; Hopp, Horacio Esteban; Reyes, Carina A. (Frontiers in Plant Science, 2021)
Citrus are among the most prevailing fruit crops produced worldwide. The implementation of effective and reliable breeding programs is essential for coping with the increasing demands of satisfactory yield and quality of the fruit as well as to deal with the negative impact of fast-spreading diseases. Conventional methods are time consuming and of difficult application because of inherent factors of citrus biology, such as their prolonged juvenile period and a complex reproductive stage, sometimes presenting infertility, self-incompatibility, parthenocarpy or polyembryony. Moreover, certain desirable traits are absent from cultivated or wild citrus genotypes. All these features are challenging for the incorporation of the desirable traits. In this regard, genetic engineering technologies offer a series of alternative approaches that allow overcoming the difficulties of conventional breeding programs. This review gives a detailed overview of the currently used strategies for the development of genetically modified citrus. We describe different aspects regarding genotype varieties used, including elite cultivars or extensively used scions and rootstocks; technical aspects of citrus genetic transformation procedures via Agrobacterium, regular physical methods and magnetofection; selection of explants considering young and mature tissues, protoplast isolation, etc. We also address current protocols and novel approaches for improving the in vitro regeneration process, which is an important bottleneck for citrus genetic transformation. This review also explores alternative emerging transformation strategies applied to citrus species such as transient and tissue localized transformation. New breeding technologies, including cisgenesis, intragenesis and genome editing by clustered regularly interspaced short palindromic repeats (CRISPR), are also discussed. Other relevant aspects comprising new promoters and reporter genes, marker-free systems and strategies for induction of early flowering, are also addressed. We provide a future perspective on the use of current and new technologies in citrus and its potential impact on regulatory processes.